The Republic of China's foreign policy towards Africa: the case of ROC-RSA relations - Tseng, San-Shiun (My University, 2009)
ABSTRACT Modern diplomacy is very different in form and substance from the diplomacy of 30 years ago. The five main components of modern diplomacy are personal diplomacy, economic diplomacy, foreign aid, conference diplomacy and public diplomacy. Personal diplomacy and conference diplomacy have much in common and have played a prominent role in the late 20th and early 21st century. Since 1949, the Republic of China (ROC) and the People’s Republic of China (PRC) have been two separate political entities competing for influence internationally. So when, in the 1960s, most African countries gained their independence and joined the UN, both the ROC and the PRC jostled to win their friendship in a zero-sum game that has lasted for the past 50 years. In the 1960s and early 1970s, the ROC used foreign aid in the form of “Operation Vanguard” as the main tool to help its African allies. It proved to be very helpful and successful and in 1969, 22 African countries had established diplomatic relations with the ROC. Yet when the ROC withdrew from the UN, its former African allies switched recognition to Beijing. By the 1980s, only South Africa, Malawi and Swaziland still maintained diplomatic ties with the ROC. In the 1990s, the ROC achieved some positive gains with ten African countries having Ambassadors in Taiwan by 1997. Also, official delegations from the ROC were established in Kinshasa, Antananarivo and Luanda. This was a setback for China, to some extent. The thesis will analyze the relations between the ROC and the five geographic areas of the African continent. Since their independence, Malawi and Swaziland have established and kept diplomatic ties with the ROC for 40 and 38 years respectively. Countries like Senegal, Lesotho, Chad and the Central African Republic have switched recognition as their needs have changed. The ROC and the Republic of South Africa (RSA) exchanged consular offices beginning in 1905 until in 1976 when they upgraded to full diplomatic relations until their demise in December 1997. During the period from the first democratic elections in RSA in April, 1994, until December, 1997, frenzied diplomatic efforts, bargaining and negotiations set a new record in world diplomatic history. Since January, 1998, the ROC and RSA have had substantive relations. Without doubt, the PRC has made much progress in its influence in the domains of international politics and its economy. Beijing released an official China-Africa policy white paper, a document remarkable for the broad range of issues it covers. As a member of the UN Security Council, China has provided large amounts of donations and foreign aid to Africa, has convened the “China-Africa Cooperation Forum” and offset foreign debt, all of which have served to squeeze the ROC’s diplomatic space in Africa. Since 2000, Liberia, Senegal and Chad have added their names to the long list of the PRC’s diplomatic allies. This thesis also examines the kinds of diplomacy that the ROC has employed in Africa to win friendships. Among them are three modern diplomatic tools which have proved the most useful and successful. These will be looked at in terms of their strength, weakness, opportunity and threat. Given that South Africa has been the most significant and influential country in Africa for the ROC, and bearing in mind that interactions between the ROC and the RSA have lasted for over a century, it is also worthwhile to further understand the highs and lows of these relations. Through the joint efforts and cooperation between governments, private sectors and third sectors, it is anticipated that bilateral relations between Taiwan and African states will continue to develop and blaze new trails.